Cu(i) substituted wurtzite ZnO: A novel room temperature lead free ferroelectric and high-: κ giant dielectric - Singh N.; Singh P. (My University, 2025)
Semiconducting wurtzite ZnO, with the highest incipient piezoelectricity is an attractive alternative choice with doping transition metal ions in the host lattice to develop novel binary ferroelectric materials that can be easily fabricated in any device architecture. Up to 8% Cu+ ion substitution on Zn2+ sites in the ZnO lattice was achieved by careful selection of raw material and adaptation of a low temperature sol-gel synthesis route for the preparation of bulk material. Phase purity and substitution of Cu+ ions in the ZnO lattice along with oxide-ion vacancy formation was confirmed using Powder X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray analysis (EDX), X-ray Photoelectron Spectroscopy (XPS) and Magnetic property measurement system (MPMS) studies. A giant dielectric constant (∼6300) was observed at 600 °C for Zn0.95Cu0.05O1-δ pellets at 100 kHz frequency. Bulk Zn0.95Cu0.05O1-δ also exhibits ferroelectricity at room temperature with remnant polarization Pr and Vc equal to 9.60 × 10-3 μC cm-2 and 3.83 × 102 V cm-1 respectively. © 2020 The Royal Society of Chemistry.